Tracing History: Jakarta, A Board Game Design - Hage, Viktoria; Wiratmo, Triyadi Guntur (Visual Communication Design, 2013)
Jakarta, with its long behind it has a lot of museums and historical landmarks which are highly potential as tourism spots. Yet such are the things notknown the locals. By comprising the whole list into a map and put it interactively in a game, the audience are expected to have direct comprehensionof local attractions, increasing their interest of Jakarta, hence a higher probability of traveling to Jakarta. The style takes a Dutch colonial approachand the colours are intentionally low in contrast to promote an old look and target young adults as they are the more probable age group to travel ontheir own funding.Keywords: history, Jakarta, tourism, board game, game design.